The association between serum tacrolimus concentrations and BK viruria in kidney transplant recipients - Napatsorn Kraivisitkul; Kajohnsak Noppakun; Chotiwit Sakuludomkan; Supavit Jirawattanapong; Siriaran Kwangsukstith; Nahathai Dukaew; Naruemon Suyayai; Mingkwan Na Takuathung; Nut Koonrungsesomboon (Scientific Reports)
Abstract The objective of this study was to examine the association between serum tacrolimus trough levels and the detection of BK viruria in kidney transplant recipients. We conducted a retrospective study and included kidney transplant recipients who underwent BK viruria screening during 2018–2021. Serum tacrolimus trough levels, urine BK viral load, and potential risk factors were collected. Statistical analysis was performed to identify the association between the serum tacrolimus trough levels and the detection of BK virus in urine (defined as positive BK viruria), as well as to determine the cumulative incidence and risk factors for BK viruria. Out of 243 recipients, 76 had positive BK viruria. The average serum tacrolimus trough level was significantly higher among the positive BK viruria group compared to the BK viruria-negative group. High HLA mismatch was identified as a risk factor for BK viruria. Approximately half of the recipients with average serum tacrolimus trough levels exceeding 10 ng/mL would develop BK viruria early. This study found an association between the average serum tacrolimus trough level and the detection of BK viruria. High HLA mismatch and an average serum tacrolimus trough level exceeding 10 ng/mL should be regarded as a risk for BK viruria.